Complete Atrioventricular (AV) Block In 15-Year-Old Girl: A Diagnostic And Therapeutic Challenge In Resource-Limited Setting - Delta Iswara Delta Iswara; Mahardhika Rafif Pratama; Anggita Dian Karera; Yislam Jaidi; Aldila Vidya Ditha Arianti (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Complete atrioventricular (AV) block is a rare and life-threatening condition in children, characterized by complete electrical dissociation between the atria and ventricles. Its diagnosis and management can be particularly challenging in resource-limited settings. A 15-year-old girl presented with chest discomfort, dyspnea, nausea, and vomiting. On examination, she was hemodynamically unstable with bradycardia (heart rate 48–58 bpm). Electrocardiography revealed a complete AV block with junctional escape rhythm. Further evaluation, including echocardiography, showed no structural heart defects and preserved ventricular function. Management included fluid resuscitation and dopamine infusion, titrated up to 20 mcg/kg/min. During titration, the patient developed ventricular tachycardia–induced bradycardia that resolved spontaneously after dose reduction. Following stabilization, the patient was referred to a higher-level facility for permanent pacemaker implantation and further investigation of the underlying etiology. This case highlights the importance of early recognition and timely intervention in pediatric complete AV block. In settings with limited resources, dopamine infusion may serve as a temporary bridging therapy when transfer is delayed, but careful monitoring is essential due to the risk of arrhythmias. Prompt diagnosis, appropriate stabilization, and early referral are crucial to reducing morbidity and preventing fatal outcomes.